2019
DOI: 10.3390/polym11061032
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hexamethylene Diisocyanate-Modified Graphene Oxide as a Nanofiller Material on the Properties of Conductive Polyaniline

Abstract: Conducting polymers like polyaniline (PANI) have gained a lot of interest due to their outstanding electrical and optoelectronic properties combined with their low cost and easy synthesis. To further exploit the performance of PANI, carbon-based nanomaterials like graphene, graphene oxide (GO) and their derivatives can be incorporated in a PANI matrix. In this study, hexamethylene diisocyanate-modified GO (HDI-GO) nanosheets with two different functionalization degrees have been used as nanofillers to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 48 publications
(69 reference statements)
1
12
0
Order By: Relevance
“…As known, raw graphite shows an intense diffraction peak at 2θ = 26.5 • , which corresponds to a d value of 0.336 nm taking into account the Bragg's equation. This peak was not observed in any of the synthesized EGOs, since it disappeared after oxidation, while a new peak appeared in the range of 9-12 • corresponding to the (001) reflection of GO [53]. The presence of this characteristic peak corroborates that all the samples were partially or completely oxidized during the electrochemical process.…”
Section: X-ray Diffraction Study Of the Egossupporting
confidence: 51%
“…As known, raw graphite shows an intense diffraction peak at 2θ = 26.5 • , which corresponds to a d value of 0.336 nm taking into account the Bragg's equation. This peak was not observed in any of the synthesized EGOs, since it disappeared after oxidation, while a new peak appeared in the range of 9-12 • corresponding to the (001) reflection of GO [53]. The presence of this characteristic peak corroborates that all the samples were partially or completely oxidized during the electrochemical process.…”
Section: X-ray Diffraction Study Of the Egossupporting
confidence: 51%
“…Besides, it was found that the covalent bonding of HDI enhances the thermal stability of GO due to chemical crosslinking between neighboring sheets, which is advantageous for long-term electronics and electrothermal device applications. These HDI-GO samples are perfect candidates as nanofillers for the development of high-performance GO-based polymeric nanocomposites [13,14].…”
mentioning
confidence: 99%
“…Pyrrole-3-carboxylic acid (C 5 H 5 NO 2 > 97%, M w = 111.1 g/mol, d 25°C = 0.862 g/cm 3 ), ammonium persulfate ((NH 4 ) 2 S 2 O 8 , 98%, M w = 228.20 g/mol, d 25°C = 1.98 g/cm 3 ), dimethylformamide (DMF, 99% C 3 H 7 NO, M w = 73.09 g/mol, d 25°C = 0.944 g/cm 3 ), N,N-dicyclohexylcarbodiimide (DCC, 99%, C 13 H 22 N 2 , M w = 206.33 g/mol; d 25°C = 1.32 g/cm 3 ), 4-dimethylaminopyrydine (DMAP, 99%, C 7 H 10 N 2 , M w = 122.17 g/mol, d 25°C = 0.96 g/cm 3 ), and thionyl chloride (SOCl 2 , 97%, M w = 118.96 g/mol, d 25°C = 1.64 g/cm 3 ) were obtained from Sigma-Aldrich (Madrid, Spain). Hexamethylene diisocyanate-modified graphene oxide (HDI-GO), with a functionalization degree of 18.1%, was synthesized according to our previous works [22,23]. The organic solvents (HPLC grade) were obtained from Scharlau S.L.…”
Section: Methodsmentioning
confidence: 99%